Technological Innovation: IoT-based Smart Greenhouse for Optimizing Red Garlic Growth - Iswahyudi, Iswahyudi; Brahma, Aji; Irawan, Dudi; Brian, Muhammad (International Applied Science, 2024)
Red garlic become a reliable commodity in Jember society. Red garlic farmers often face some emerging problems such as the influence of extreme weather on the growth of red garlic crops. The success of growing garlic depends on several factors including maintenance temperature, soil humidity, nutrition and use of medicines. (fungicide). One of the technological developments that can be used in agriculture is the development of greenhouses as a monitoring and control system to control the growth of garlic crops. The presence of this innovation is expected to help carry out automatic spraying, irrigation, medication activities using an Internet of Things-based application system. Components used in this system are Arduino and ESP32 microcontroller, Dht22 sensor as temperature controller, Yl-69 soil moisture sensor, and soil pH sensor to monitor soil fertilizer elements. The device can monitor soil humidity, temperature, medication, and soil pH through the Blynk app. From the results of this study, plants grown in greenhouses have a 100% presentation rate with 30 seeds and are growing fertile. This is better than planting on caterpillars and polybags with a growth rate of 84% and 90% or only 25 seed and 27 seed remains.Red Garlic